Availability of solar energy for natural lighting and electricity / Mohd Nazli Abdul Ghani - Abdul Ghani, Mohd Nazli (2002)
The application of Solar Photovoltaic (PV) is not widely used in Malaysia especially in the rural areas where no electricity is available. This study focuses in the viability of using solar PV technologies for lighting in building. The objective of this study are to determine the typical solar radiation available in Klang Valley that is needed to convert to electrical energy using solar panel; to determine the amount of time and solar energy to recharge the batteries and to determine the cost of using this technologies as compared to conventional electrical energy.